Heavy metal concentrations in the razor clams (solen spp) from Muara Tebas, Sarawak - Kanakaraju, Devagi; Jios, Connie; Mohd Long, Shabdin (Pusat Pengajian Sains Kimia dan Teknologi Makanan Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2008)
The razor clams (Solen spp) or locally known as ‘ambal’ in Sarawak collected from Muara Tebas were studied for their heavy metals contents in tissues and shells. Sediment samples were also tested for their metal contents. Concentrations of Pb, Fe, Zn, Cu, Cd and Mn were determined by using Flame Atomic Absorption Spectrophotometer (FAAS). Tissues of razor clams showed highest concentrations of Fe and Zn, while shells accumulated highest concentrations of Pb and Mn. The lowest metal concentrations found were Cu and Cd. In general, the levels of metals in ‘ambal’ were within the permissible limit recommended by international standard, the Food and Agricultural Organization (FAO). However, the study revealed that the sediments at Muara Tebas fall under the category of slightly polluted (for Pb) when compared to the guidelines suggested by United States Environment Protection Agency (USEPA).